2012
DOI: 10.1002/jhet.908
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Clean Procedure for Three‐Component Syntheses of Spiro{pyrido[2,1‐b]benzothiazole‐3,3′‐indolines} and Spiro{thiazolo[3,2‐a]pyridine‐7,3′‐indolines} in Aqueous Medium

Abstract: A simple and efficient one-pot three component synthesis of spiro{pyrido[2,1-b]benzothiazole-3,3 0 -indoline} and/or spiro{thiazolo[3,2-a]pyridine-7,3 0 -indoline} derivatives were carried out by the reaction of 2-mercaptoaniline and/or mercaptoacetic acid, malononitrile, and a series of 2-oxoindoline-3-ylidines in aqueous medium. This method is of great value because of its environmentally benign character, high yield processing, and easy handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Based on these prior observations, we postulated that a Schiff base containing both indoline and pyran pharmacophores could be very effective for antimicrobial and anticancer activity. In this paper and as a consequence of our previous work on the green synthesis of different spiroheterocyclic (Hussein 2013 ; Hussein and El-Khawaga 2012 ; Hussein 2012 ; El-Zohry et al 2008b , c , 2009 ), and bioactive heterocyclic compounds (Hussein et al 2015b ; Hussein and Abdel-Monem 2011 ), we investigated a novel green and efficient protocol that was developed for the synthesis of some Schiff bases ( 5a – l ) by the condensation of spiro[indoline-3,4′-pyran]-3′-carbonitrile derivatives ( 3a – c ) with aromatic aldehydes ( 4a – d ) using ammonium chloride (10 mol%) in refluxing ethanol as shown in Scheme 2 and Table 1 . The antimicrobial and cytotoxic properties of the prepared compounds were screened.…”
Section: Introductionmentioning
confidence: 72%
“…Based on these prior observations, we postulated that a Schiff base containing both indoline and pyran pharmacophores could be very effective for antimicrobial and anticancer activity. In this paper and as a consequence of our previous work on the green synthesis of different spiroheterocyclic (Hussein 2013 ; Hussein and El-Khawaga 2012 ; Hussein 2012 ; El-Zohry et al 2008b , c , 2009 ), and bioactive heterocyclic compounds (Hussein et al 2015b ; Hussein and Abdel-Monem 2011 ), we investigated a novel green and efficient protocol that was developed for the synthesis of some Schiff bases ( 5a – l ) by the condensation of spiro[indoline-3,4′-pyran]-3′-carbonitrile derivatives ( 3a – c ) with aromatic aldehydes ( 4a – d ) using ammonium chloride (10 mol%) in refluxing ethanol as shown in Scheme 2 and Table 1 . The antimicrobial and cytotoxic properties of the prepared compounds were screened.…”
Section: Introductionmentioning
confidence: 72%
“…A simple and efficient one‐pot three components synthesis of spiro[thiazolo[3,2‐ a ]pyridin]‐7,3'‐indoline derivatives was carried out from the reaction of 2‐mercaptoacetic acid, malononitrile, and a series of 2‐oxoindoline‐3‐ylidines in aqueous medium. This method is of great value because of its environmentally benign character, high yielding process, and easy handling (Scheme ).…”
Section: Condensed 4‐thiazolidinonesmentioning
confidence: 99%
“…The view of our design of the newly synthesized compounds in this research point is based on other biologically active heterocycles reported in the field of microbial and cancer therapy such as pyrazoles [15,16], triazoles [17,18], and Schiff bases [19][20][21]. In continuation of our work on the synthesis of heterocyclic systems [22][23][24][25] and for biological evaluations [26,27], we considered it attractive to synthesize some novel substituted 6′-(4-chlorophenyl)-3,4′-bipyridine-3′-carbonitriles and evaluation of their antimicrobial and cytotoxic activity. 2-(6′-(4-Chlorophenyl)-3′-cyano-3,4′-bipyridin-2′-yloxy) acetohydrazide (3) was prepared and used as a building block for the synthesis of the title compounds.…”
Section: Introductionmentioning
confidence: 99%